Классификация символов в алгоритмах сжатия изображения текста и системы оптического распознавания - Иванов, В. Г.; Ломоносов, Ю. В.; Любарский, М. Г. (НТУ "ХПИ", 2012)
Показано, что получение минимально возможного количества классов при двухэтапной классификации изображений символов текста дает возможность уменьшить ошибку распознавания текста системами оптического распознавания практически на 50% по сравнению с форматом ВМР и около 35% – 40% по сравнению с классификацией в формате DjVu.

It is proved that the forming of the possible minimum of the quantity of classes within two-stage classification of the text symbol images allows to minimize the error of text recognition by the systems of optical recognition for about 50% as comparing with the BMP format and about 35% – 40% as comparing with classification within DjVu format.
Classification of characters is in the algorithms of compression of text and system of optical recognition
Keywords: двухэтапная классификация; алгоритм сжатия; оптическое распознавание; изображения символов; classification; images of characters; optical recognition